Leachate treatment using subsurface flow and free water surface constructed wetland systems - Kamarudzaman, Ain Nihla (2006)
The sanitary landfill plays a most important role in the framework of solid waste disposal. Discharge of leachate into the environment constitutes the major environmental concern associated with sanitary landfill and need to prevent. Based on previous study, constructed wetland system has high efficiency in treating landfill leachate with low operating and maintenance cost. A combination system utilizing a subsurface flow (SSF) wetland followed by a free water surface (FWS) wetland was studied to treat landfill leachate. In this study, Limnocharis flava and Eichhornia crassipes were used as aquatic plants in wetland system. SSF and FWS constructed wetland systems were arranged in series and operated for around 3 weeks with hydraulic loading rate (HLR) (0.13 m/cycle/day). Two lab scale systems of constructed wetlands were used in the experiments. Performance of SSF-FWS constructed wetland was evaluated with comparison to a Control system (unplanted). The result demonstrated that a combination system utilizing a SSF-FWS constructed wetland systems have shown higher performance in treating leachate landfill. The result demonstrated that the removal efficiency of pollutants in leachate using Limnocharis flava and Eichhornia crassipes in SSF-FWS constructed wetlands were NH4-N (93.1%), NO3-N (96.4%), PO43- (95.9%), Fe (99.5%) and Mn (97.7%). Removal efficiency of SS and turbidity were achieved 87.3% and 99.6%, respectively. Limnocharis flava had higher capacity to accumulate heavy metals (Fe and Mn) in leachate constituents compared than Eichhornia crassipes. From the study, it shows that Fe and Mn uptake is more significant in roots compare to leaves. This study concludes that SSF-FWS constructed wetlands can increase the performance of nutrient and heavy metal removal and also enhance leachate water quality.